Comparative analysis of cardioprotective effects of two renal denervation techniques - T. M. Ripp; S. E. Pekarskiy; A. E. Baev; T. R. Ryabova; E. I. Yaroslavskay; A. Yu. Falkovskaya; E. S. Sitkova; V. A. Lichikaki; I. V. Zubanova; M. A. Manukian; L. I. Gapon; V. F. Mordovin (Российский кардиологический журнал)
Aim. To compare cardioprotective effects of two renal denervation (RD) techniques: main renal artery or its branches after bifurcation in patients with resistant hypertension (RH).Materials and methods. This randomized double-blind clinical (ClinicalTrials. gov. identifier: NCT02667912) study with a follow-up of 12,3±1,6 months included 55 patients with RH, which was divided into 2 groups: group 1 (n=27) — main renal artery denervation; group 2 — RD of branches. Mean age of patients was 57,3±9,5 and 56,4±9,3 years, respectively. We assessed structural and functional cardiac characteristics using two-dimensional speckle-tracking echocardiography (STE).Results. Initially, the patients in the groups did not differ in terms of studied parameters and therapy. After RD in both groups, the levels of myocardial stress significantly decreased; 95% confidence interval: after main renal artery denervation — systolic [-4802; -2896], diastolic [-3264; -2032] dyne/cm2; after RD of branches — [-6324; -5328] and [-4021; -2521] dyne/cm2, respectively (p=0,001 and 0,024, respectively). After main renal artery denervation, there was a decrease in the left ventricular (LV) wall thickness (interventricular septum [1,06; -0,62] and posterior wall [0,12; -0,62]) in comparison with RD of branches ([-0,68; -1,28] and [-0,68; -1,06], respectively). These differences were significant: p=0,023 and 0,021, respectively. After distal RD, decrease in the LV mass was observed more often by 21,2%, an increase in the LV mass was 2 times less frequent. Restoration of diastolic function was more common in patients after distal RD than main renal artery denervation (26% vs 13%, respectively). According to pilot analysis, STE parameters was also improved.Conclusion. Twelve months after distal RD, compared with the main renal artery denervation, the LV wall thickness, number of patients with LV hypertro -phy, and diastolic dysfunction decreased significantly greater. Two-dimensional STE revealed improvement of cardiac parameters. The results require further research.